2021
DOI: 10.1371/journal.pone.0251746
|View full text |Cite
|
Sign up to set email alerts
|

Available medications used as potential therapeutics for COVID-19: What are the known safety profiles in pregnancy

Abstract: Background Medications already available to treat other conditions are presently being studied in clinical trials as potential treatments for COVID-19. Given that pregnant women are excluded from these trials, we aimed to investigate their safety when used during pregnancy within a unique population source. Methods Using the population-based Quebec Pregnancy Cohort, we identified women who delivered a singleton liveborn (1998–2015). Taking potential confounders into account including indications for use, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
(79 reference statements)
1
8
0
Order By: Relevance
“…Alberta and Quebec systematically reported higher annual rates of malformations, 16.4% and 10.4%, respectively. This is consistent with Quebec’s founders’ effect [ 16 ] (i.e. a relatively small number of French settlers were ancestors of a large number of families in France), and Zhao et al [ 17 ]; it could also be explained in part by the fact that women of lower socio-economic status have poorer health or poor lifestyle habits.…”
Section: Discussionsupporting
confidence: 89%
“…Alberta and Quebec systematically reported higher annual rates of malformations, 16.4% and 10.4%, respectively. This is consistent with Quebec’s founders’ effect [ 16 ] (i.e. a relatively small number of French settlers were ancestors of a large number of families in France), and Zhao et al [ 17 ]; it could also be explained in part by the fact that women of lower socio-economic status have poorer health or poor lifestyle habits.…”
Section: Discussionsupporting
confidence: 89%
“…QPC data on prescriptions filled ( Zhao et al, 2017 ), MCM ( Blais et al, 2013 ), gestational age ( Vilain et al, 2008 ) and birth weight ( Vilain et al, 2008 ) have been validated. We have adjusted for all known and measurable potential confounding variables for unfavorable pregnancy outcomes, including maternal chronic comorbidities, indications for study medication uses, lifestyles variables including the use of alcohol, tobacco, illicit substances, and high dose folic acid; adjustment was also made on health care utilization, which is considered as a proxy for diseases severity ( Bérard et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both the PPV and NPV for medication use were high within the QPC. Because we only included pregnant women covered by the Quebec prescription drug insurance plan, generalizability of results to those covered by private medication insurance could be affected ( Bérard et al, 2021 ). However, validation studies have shown that publicly insured pregnant women have similar characteristics and co-morbidities with those who have private drug insurance plans ( Bérard and Lacasse, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although, compared to prednisolone, methylprednisolone achieves higher lungs concentrations [156], based on the RECOVERY trial findings, oral prednisolone, and intravenous hydrocortisone are recommended for moderate to severe cases of COVID-19 [157]. WHO recommends oral dexamethasone or intravenous hydrocortisone in severe cases of COVID-19, but studies have recommended against dexamethasone during pregnancy, which is linked with an increased risk of prematurity and adversely affects skeletogenesis [158,159]. Limited data support dexamethasone in postpartum patients; therefore, methylprednisolone is recommended instead [160].…”
Section: Treatment and Drug Safetymentioning
confidence: 99%